Aktivitas Antioksidan Ekstrak Etanol Batang Ciplukan (Physalis angulata L.) menggunakan DPPH - Aviah, Annisaa Ainun; Rahmawati, Rahmawati; Syarif, Sukmawati (PHARMACY UMI JOURNAL SYSTEM, 2024)
Ciplukan (Physalis angulata L.) is a member of the Solanaceae family which is a type of eggplant. Ciplukan contains several chemical substances that are useful for treatment such as fisalin, saponins, alkaloids and flavonoids. Ciplukan is used as an antihyperglycemic, antibacterial, antiviral, immunostimulant and immunosuppressant (immunomodulator), anti-inflammatory, antioxidant, analgesic and cytotoxic. The purpose of this study was to determine the antioxidant effectiveness of the ethanol extract of ciplukan stems using the DPPH (1,1 diphenyl-2-picryhidrazyl) method. Samples were extracted by maceration method using 96% ethanol solvent. For each extract, a quantitative test was carried out and the absorbance was measured using a UV-Vis spectrophotometer at a wavelength of 514 nm with quercetin as a comparison. The percent value of the ciplukan stem yield obtained was 10.654%. From the results of the research on the antioxidant activity of the ethanol extract of Ciplukan stem (Physalis angulata L.) a regression value of y = 0.0433x + 41.698 was obtained with an R2 value = 0.9972 and an IC50 value of 191,732 ppm. The results of this study indicate that the ethanol extract of ciplukan (Physalis angulata L.) stem has an antioxidant effect in the moderate category.